Schizophrenia and Bipolar Illness in the Relatives of University Scientists: An Epidemiological Report on the Creativity-Psychopathology Relationship - Parnas, Josef; Sandsten, Karl Erik; Vestergaard, Claus Høstrup; Nordgaard, Julie (Frontiers in Psychiatry, 2019)
A potential link between creativity and mental illness has been a longstanding topic for human studies and empirical research. The major problem is defining creativity and establishing its measurable indicators. A few high-quality epidemiological studies have been undertaken and point to a link between creativity and vulnerability to mental illness. Demonstrating such a shared vulnerability could expand our understanding of mental illnesses and open up new avenues of empirical research. In this epidemiological study, we defined scientists (academics) at the universities as individuals assumed to exhibit “more creativity” than the background population. In a register coupling with a population of 588.532 people, we examined successful university academics’ first- and second-degree relatives for diagnosed mental disorders and compared those figures with controls from the background population controlling for educational level. The relatives of the academics had significantly increased risk of suffering from schizophrenia or bipolar disorder. For bipolar disorder, it is perhaps temperamental features and high energy levels that contribute to this association. In the case of schizophrenia, the mediating bridge may involve an amplification of human tendency to question the obvious and “taken-for-granted”. Creativity and an increased risk for mental disorders seem to be linked by a shared vulnerability that is not manifested by clinical mental disorders in the academics.